THE VIETNAMESE AGENDA OF ADOPTING ENGLISH AS A MEDIUM OF INSTRUCTION - Nha, Vu Thi Thanh (VNU Journal of Foreign Studies; Vol 33 No 3, 2017)
English as a medium of instruction has been recently adopted in Vietnam's educational system. This gives rise to a concern as why a Vietnamese-speaking country decided to endorse EMI programs as one of its critical educational reforms. This paper aims to analyse the literature to explore the various agendas (social, economic, political, and educational) that underlie the EMI expansion. It examines the world literature as a framework of reference for analysing the Vietnamese case. Hopefully, the paper will provide policymakers and implementers insights into the EMI processes to maximise the benefits and avoid pitfalls.